The effect of Al on the hydrogen sorption mechanism of LiBH4 - Friedrichs, O.; Kim, J. W.; Remhof, A.; Buchter, F.; Borgschulte, A.; Wallacher, D.; Cho, Y. W.; Fichtner, M.; Oh, K. H.; Zuettel, A. (ROYAL SOC CHEMISTRY, 2009)
We demonstrate the synthesis of LiBH4 from LiH and AlB2 without the use of additional additives or catalysts at 450 degrees C under hydrogen pressure of 13 bar to the following equation: 2LiH + AlB2 + 3H(2) <-> 2LiBH(4) + Al. By applying AlB2 the kinetics of the formation of LiBH4 is strongly enhanced compared to the formation from elemental boron. The formation of LiBH4 during absorption requires the dissociation of AlB2, i.e. a coupled reaction. The observed low absorption-pressure of 13 bar, measured during hydrogen cycling, is explained by a low stability of AlB2, in good agreement with theoretical values. Thus starting from AlB2 instead of B has a rather low impact on the thermodynamics, and the effect of AlB2 on the formation of LiBH4 is of kinetic nature facilitating the absorption by overcoming the chemical inertness of B. For desorption, the decomposition of LiBH4 is not indispensably coupled to the immediate formation of AlB2. LiBH4 may decompose first into LiH and elemental B and during a slower second step AlB2 is formed. In this case, no destabilization will be observed for desorption. However, due to similar stabilities of LiBH4 and LiBH4/Al a definite answer on the desorption mechanism cannot be given and neither a coupled nor decoupled desorption can be excluded. At low hydrogen pressures the reaction of LiH and Al gives LiAl under release of hydrogen. The formation of LiAl increases the total hydrogen storage capacity, since it also contributes to the LiBH4 formation in the absorption process.
Keywords: ALUMINUM DIBORIDE; STORAGE; DESTABILIZATION